3*2*4 = 24
the answer is 6
5x - 16 = 3x2x - 16 = 02x = 16x = 8
2x + x(x + x) + xx + x + x = 3x2x + x = 3x* * * * *No, no, no! The correct answer is:x2 + x = x(x + 1).It is sometimes best to test answers with various substitution values.x2 + x = 3x, only when x = 0 or 2; but not otherwise.
I assume you have : 5x - 9 = 3x + 11This is a single algebraic expression.Subtract 3x from both sides.5x - 9 - 3x = 3x + 11 - 3x2x - 9 = 11Add 9 to both sides :2x - 9 + 9 = 11 + 92x = 20x = 10
3x + y = 4x + y = 0solve for yy = -3x +4y = -xsubstitute y = -x into y = -3x +4, so the result is: -x = -3x +4solve for x-1x = -3x +4+3x +3x2x = 4--------2x = 2then plug the x-value into one of the bolded equations and solve for y.I chosey = -xy = -(2)y = -2so the final answer is the ordered pair (2, -2)